The Future of Schizophrenia Pharmacotherapeutics: Not So Bleak - Carpenter, William T. (Medknow Publications & Media Pvt Ltd, 2012)
Chlorpromazine efficacy in schizophrenia was observed 60 years ago. Advances in pharmacotherapy of this disorder have been modest with effectiveness still limited to the psychosis psychopathology and mechanism still dependent on dopamine antagonism. While a look backward may generate pessimism, future discovery may be far more robust. The near future will see significant changes in paradigms applied in discovery. Rather than viewing schizophrenia as a disease entity represented by psychosis, the construct will be deconstructed into component psychopathology domains. Each domain will represent a clinical target for aetiologic and therapeutic discovery. Research on pathophysiology will shift to the neural circuit level in relation to specific behavioural constructs. Progress at the molecular, genetic, cellular and network levels will be more robust. The behavioural paradigm will map on to the deconstructed clinical paradigm and in the process discovery will cut across current classification boundaries.